2009
DOI: 10.1590/s1415-43662009000600014
|View full text |Cite
|
Sign up to set email alerts
|

Alteração química do solo irrigado por aspersão e gotejamento subterrâneo e superficial com água residuária

Abstract: Propôs-se, neste trabalho, avaliar a variação dos constituintes químicos do solo devido à aplicação de água residuária e água de um depósito de fonte superficial, durante dois ciclos da alface (Lactuca sativa L.), cv "Elisa", utilizando-se os sistemas de irrigação por aspersão, gotejamento subterrâneo e superficial. Analisaram-se as camadas de solo de 0-0,10 e 0,10-0,20 m, aos 6, 26 e 46 dias após o transplantio no 1° ciclo e aos 7, 27 e 49 dias após o transplantio, no 2° ciclo. Os resultados demonstraram que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
20

Year Published

2013
2013
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 18 publications
2
9
1
20
Order By: Relevance
“…These results corroborate with Leal et al (2009a) and Herpin et al (2007) information, who detected no changes in the magnesium levels between layers from 10 cm to 40 cm in sugarcane and coffee crops, respectively. Sandri et al (2009) found no differences between the Mg 2+ concentrations in the depth of 0-10 and 10-20 cm for lettuce cultivation.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…These results corroborate with Leal et al (2009a) and Herpin et al (2007) information, who detected no changes in the magnesium levels between layers from 10 cm to 40 cm in sugarcane and coffee crops, respectively. Sandri et al (2009) found no differences between the Mg 2+ concentrations in the depth of 0-10 and 10-20 cm for lettuce cultivation.…”
Section: Resultsmentioning
confidence: 64%
“…Although castor beans can absorb significant amounts of Ca 2+ when grown in the presence of sewage sludge (Chiaradia et al, 2009), this nutrient is usually present in large amounts in wastewater from households, reaching in some cases concentrations higher than Na + , as observed in other studies (Medeiros et al, 2007;Sandri et al, 2009). These high levels in wastewater may lead to accumulation, even under crop cultivation , as found by Herpin et al (2007).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The use of sewage effluent in agricultural irrigation has been presented as a viable alternative for the disposal of wastewater, especially for its agronomic benefits, in which the water supply of vegetables and provision of essential nutrients for plant growth, appear as the main benefits the reuse (KALAVROUZIOTIS et al, 2009;FONSECA et al, 2007;SANDRI et al, 2009;DEON et al 2010, SANTOS et al, 2010.…”
Section: Introductionmentioning
confidence: 99%